Boycott intention on Israel funding producrts : pre and post of Palestine issue awareness - Abdul Gafur Abdul Rahmat Julianto, 1993- 638642; Zuraidah Sulaiman, supervisor 598934; Fakulti Pengurusan 538641 (2016)
Project Paper (Sarjana Muda Pengurusan (Pemasaran)) - Universiti Teknologi Malaysia, 2016